The Korean War: Just or Unjust? - Bisek, Matt (My University, 2014)
This paper examines the seven rules of the just war theory and applies them to the Korean War (1950-53). The seven rules of the just war theory are just cause, right intention, legitimate authority, public declaration, last resort, probability of success, and proportionality. This analysis demonstrates that the Korean War was a just war in relation to the principles of the just war theory. A brief history of the evolution of the just war theory from Cicero and leading up to the Conclusion of World War II (1945) will be given. Each rule will be have a detailed description in regards to how the United States adhered to it. The following research serves as a basis to prove the validity that the Korean War was a just war.
Keywords: Korean War, 1950-1953; Just war doctrine